Health Promotion in Efforts to Prevent Stunting in the First 1000 Days of Life (HPK) at Puskesmas X Koto 1 Tanah Datar Regency - Wira Iqbal; Kamal Kasra; Dicki Kurnia Pratama; Dini Nur Annisa; Dyki Gymnasdian; Fajrul Khairi; Hanifa Eka Putri (Warta Pengabdian Andalas, 2024)
Stunting, a persistent global nutritional issue from inadequate care and nutritional intake, becomes evident when a child ages two. Tanah Datar recorded a 21.5% stunting rate in 2022, prompting a targeted service to enhance the literacy of pregnant women, mothers of toddlers, and cadres about the critical first 1000 days of life. Utilizing an interactive game, Emotional Demonstration, and drawing on four modules from the Global Alliance for Improved Nutrition (GAIN), the service employed printed modules and game equipment. Held on 10 June 2023 at Wali Nagari Pandai Sikek Hall, the event gathered 20 participants, including pregnant women, mothers, cadres, and X Koto Community Health Center officers. Activities commenced with a pre-test, followed by interactive game-based education, and concluded with a post-test. The community service positively contributed to increased health literacy and awareness in the first 1000 days, validated by significant T-test results (p-value = 0.001), indicating a substantial knowledge improvement post-intervention.